2016
DOI: 10.1016/j.addbeh.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

History of abuse and risky sex among substance users: The role of rejection sensitivity and the need to belong

Abstract: This study investigates abuse and rejection sensitivity as important correlates of risky sexual behavior in the context of substance use. Victims of abuse may experience heightened sensitivity to acute social rejection and consequently engage in risky sexual behavior in an attempt to restore belonging. Data were collected from 258 patients at a substance use treatment facility in Washington, D.C. Participants' history of abuse and risky sexual behavior were assessed via self-report. To test the mediating role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…In another line of research, we explored engagement in RSB as a means to intimacy and communion goals. In several studies, across community samples, college students, and substance users, we found that women who have experienced interpersonal violence were more likely to engage in RSB (Woerner, Kopetz, & Arriaga, in preparation;Woerner, Kopetz, Lechner, & Lejuez, 2016). This may be the case because interpersonal violence potentially disrupts individuals' expectations of secure relationships and may result in discomfort with closeness (i.e., avoidance).…”
Section: Risky Sexual Behavior As a Function Of Goalsmentioning
confidence: 94%
“…In another line of research, we explored engagement in RSB as a means to intimacy and communion goals. In several studies, across community samples, college students, and substance users, we found that women who have experienced interpersonal violence were more likely to engage in RSB (Woerner, Kopetz, & Arriaga, in preparation;Woerner, Kopetz, Lechner, & Lejuez, 2016). This may be the case because interpersonal violence potentially disrupts individuals' expectations of secure relationships and may result in discomfort with closeness (i.e., avoidance).…”
Section: Risky Sexual Behavior As a Function Of Goalsmentioning
confidence: 94%
“…This point of view can also explain the heterogeneity in results with respect to the few studies that have applied the BART: these studies were either not able to find shifts in risk taking following experiences of child abuse [14], reported increased risk behavior associated with child abuse [12] and PTSD [11], or reported effects in the opposite direction [13]. …”
Section: Discussionmentioning
confidence: 99%
“…From a social perspective, rejection includes aspects of punishment and increases the avoidance motivation that is salient for high BIS individuals [ 42 ]. In addition to BIS, a history of abuse may markedly alter an individual’s sensitivity to social rejection [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%